2000
DOI: 10.1177/104649640003100106
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Carron and Brawley

Abstract: Carron and Brawley have raised questions about the research methodology used by Carless and DePaola. In addressing their comments, the author begins by raising the issues of level of theory, level of data collection, and level of analysis. The author argues that there is increasing evidence that the most appropriate level of conceptualization of cohesion is the group level rather than the individual level. Following is a discussion of methodological issues raised by Carron and Brawley: (a) temporal issues asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…However, it also should be noted that there has been some debate about the overall utility of examining perceptions of "individual attractions to the group" in cohesion research. While it is beyond the scope of the present paper to provide a comprehensive overview of this issue (for examples of this discussion, see Carless, 2000;Carron & Brawley, 2000;Dion, 2000), our results are also unlikely to clarify whether the current lack of emergence of an individual attractions-group integration separation is due to developmental or conceptual issues. At this point, it is sufficient to note that (a) the current study was initially based on a strong theoretical foundation provided by Carron and colleagues (1985) that is supported by over 20 years of research, (b) both task and social dimensions contain items originally classified at individual attractions and group integration levels, (c) it appears youths do not perceive separation between the constructs of group integration and attractions to the group, and (d) a number of conceptual issues remain in the examination of cohesion (Dion, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…However, it also should be noted that there has been some debate about the overall utility of examining perceptions of "individual attractions to the group" in cohesion research. While it is beyond the scope of the present paper to provide a comprehensive overview of this issue (for examples of this discussion, see Carless, 2000;Carron & Brawley, 2000;Dion, 2000), our results are also unlikely to clarify whether the current lack of emergence of an individual attractions-group integration separation is due to developmental or conceptual issues. At this point, it is sufficient to note that (a) the current study was initially based on a strong theoretical foundation provided by Carron and colleagues (1985) that is supported by over 20 years of research, (b) both task and social dimensions contain items originally classified at individual attractions and group integration levels, (c) it appears youths do not perceive separation between the constructs of group integration and attractions to the group, and (d) a number of conceptual issues remain in the examination of cohesion (Dion, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Further, these concepts apply to task and social dimensions of group work. Carless (2000) supported Carrón and Brawley's (2000) position but encouraged researchers to clarify not only conceptual definitions but to identify linkages between cohesion and other constructs. In on-going groups, found a positive relationship between cohesion and members' argumentativeness and a negative relationship between cohesion and tendencies to be verbally aggressive.…”
Section: Cohesionmentioning
confidence: 92%
“…DeStephen and Hirokawa reported that the five dimensions accounted for 60% of the variance, with the largest segment of the variance (32.3%) attributed to feelings about the group decision and the second largest (14%) attributed to individual participation. Although the scales discussed above have been useful, it seems appropriate to examine relational communication satisfaction apart from frameworks that designed instruments to measure communication satisfaction, consensus or cohesion (see Carrón & Brawley, 2000;Carless, 2000, for discussion of cohesion). According to Key ton (2000), affective orientation of group communication "deserves to be considered as a dimension equal in importance to task orientation" (p. 388).…”
mentioning
confidence: 99%
“…Cohesion is seen as an important group dynamic, as it affects the group's performance in a positive manner, along with providing individual work satisfaction and psychological well-being. 1 While cohesion was described in initial studies as a one-dimensional construct, later studies have revealed that cohesion is a construct that is actually multi-dimensional. [2][3][4][5][6] While Carron approaches the concept from the multi-dimensional perspective and defines it as "a dynamic process which is reflected in the tendency for a group to stick together and remain united in the pursuit of its goals and objectives," Campbell and Martens define it as "the stimulated mutual pull that enables the individuals in the group to stick together and desire to always work together."…”
mentioning
confidence: 99%